Atypical Presentation of a Large Aortopulmonary Window in a Very Low Weight and Preterm Born Infant - Schumacher, Katja; Meier, Sabine; Borger, Michael A; Kostelka, Martin; Vollroth, Marcel (Archives of Clinical and Medical Case Reports, 2022)
Abstract not available in the source database.